KONSELING INDIVIDU MELALUI PENDEKATAN TERAPI REALITAS UNTUK REMAJA YANG KECANDUAN GADGET - Shilhiya Khairi Nafs; N Nurjannah (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2022)
The purpose of this study was to determine the process and results of counseling carried out by counselors on a counselee who is experiencing gadget addiction through individual counseling based on reality therapy. The method used in this study is a descriptive qualitative method which explains the process carried out by counselors when providing counseling to clients who are addicted to gadgets. The results showed that initially the diagnosis showed that there were symptoms of addiction to gadgets based on their daily habits. These habits result in antisocial children, neglecting schoolwork, chores at home, and unstable emotions, even denying their parents. Furthermore, the counseling process is carried out on the counselee with the technique of changing his habits by controlling himself and having responsibility for the decisions chosen through the reality therapy approach. The result of the counseling process is that the client has started to control himself by making a schedule for studying, playing with friends and family, also playing gadgets. When one of the schedules he made was violated by himself, then there were consequences he had to bear.